A novel missense variant in the RASGRP2 gene in patients with moderate to severe bleeding disorder. (3rd July 2020) - Alharby, Essa; Bakhsh, Mohammad A; Albalawi, Alia M; Almutairi, Sultan O; Hashmi, Jamil A; Basit, Sulman
Abstract: Inherited platelet function disorder-18 (IPD-18) is a relatively new non-syndromic autosomal recessive bleeding disorder. It is characterized by deficient or dysfunctional CalDAG-GEFI protein. The distinctive feature of the disease is impaired platelet aggregation in response to multiple physiologic agonists. We here report a family with a platelet-type bleeding disorder and a novel mutation in the RASGRP2 gene. The overall bleeding score for the affected individuals was 15 and 12. Based on the initial diagnosis of Glanzmann thrombasthenia, targeted sequencing of integrin subunit alpha 2b and integrin subunit beta 3 encoding genes ITGA2B and ITGB3 were carried out in both affected members of a family. Sequence alignment failed to identify the disease-causing variant(s) in both genes. Therefore, whole exome sequencing in one affected individual was performed. Data analysis detected a novel homozygous missense variant (c.956C>T; p.Pro319Leu) in the exon 9 of the RASGRP2 gene. Five additional individuals of a family including both parents, an affected individual and two asymptomatic individuals were Sanger sequenced for the variant (c.956C>T). The variant segregates in the family in an autosomal recessive manner. Several in silico tools predicted the variant as pathogenic. Protein modeling studies suggest that the mutation (p.Pro319Leu) cause a conformational change in the loop structure of the RasGEF domain of the CalDAG-GEFI protein. Reported variants in the RasGEF domain impair expression and/or nucleotide exchange activity of CalDAG-GEFI protein and thus inhibit the activation of Rap1 protein required for platelet adhesion and hemostatic plug formation.